UJI STABILITAS FISIK SEDIAAN FACE SPRAY EKSTRAK ETANOL 96% BIJI BUAH ALPUKAT (Persea Americana Mill) DENGAN VARIASI KONSENTRASI GLISERIN - Eka Pafitri, Anisa; Kenanga Sari, Gigih; Purwanjani, Wahyu (Nusantara Hasana Journal, 2026)
Avocado seeds contain secondary metabolite compounds in the form of alkaloids, flavonoids, saponins, tannins, triterpenoids and steroids. To moisturize and protect the face, spray face spray. The natural ingredients of avocado seeds can be used as a face spray because they contain antioxidants. This study aimed to analyze physical stability of Persea Americana seed extract face spray preparation against variations in glycerin concentration carried out for 6 cycles. In this research, avocado seed extract was obtained using the maceration method and formulated into a face spray preparation with varying glycerin concentrations of 20%, 25% and 30%. The physical stability test of avocado seed extract was carried out using the cycling test method for 6 cycles. P. americana seed extract could be formulated as a face spray. Variations in glycerin concentration affected the results of stability tests on face spray preparations of P. americana seed extract. The F3 formulation had the best results in the face spray preparation of avocado seed extract. Avocado seed extract could be formulated in a face spray with a concentration of 30% to give the best results